2011
DOI: 10.1002/chem.201101260
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reactions: A Controlled Approach for Carbon Nanotube Functionalization

Abstract: Controlled functionalization of carbon nanotubes (CNTs) through the use of cycloaddition reactions is described. By employing various cycloaddition reactions, a wide range of molecules could be coupled onto CNTs without disruption of the structural integrity as well as with a statistical distribution of functional groups onto the surface of the CNTs. The cycloaddition reactions represent an effective and tailored approach for preparing CNT-based advanced hybrid materials that would be useful for a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 72 publications
0
39
0
1
Order By: Relevance
“…Since the Iijima's discovery [1], single-walled carbon nanotubes (SWCNTs) have become a focus of theoretical and experimental studies owing to their perfect structures and unique properties as well as potential applications. SWCNTs demonstrate outstanding mechanical, physical, chemical, thermal, electronic, and optical properties, which predetermine their great influence on nanotechnologies [2][3][4][5][6][7][8][9]. It was found that their Young's modulus is ~ 1 TPa [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Iijima's discovery [1], single-walled carbon nanotubes (SWCNTs) have become a focus of theoretical and experimental studies owing to their perfect structures and unique properties as well as potential applications. SWCNTs demonstrate outstanding mechanical, physical, chemical, thermal, electronic, and optical properties, which predetermine their great influence on nanotechnologies [2][3][4][5][6][7][8][9]. It was found that their Young's modulus is ~ 1 TPa [6].…”
Section: Introductionmentioning
confidence: 99%
“…SWCNTs demonstrate outstanding mechanical, physical, chemical, thermal, electronic, and optical properties, which predetermine their great influence on nanotechnologies [2][3][4][5][6][7][8][9]. It was found that their Young's modulus is ~ 1 TPa [6]. However, there exist some deviations of Young's modulus values both experimentally obtained and theoretically predicted.…”
Section: Introductionmentioning
confidence: 99%
“…However, difficulties involved in dispertion and solubilization of CNTs, largely owing to strong force interactions between the nanotubes, continue to present obtacles to thier practical application. To improve the dispersion of CNTs, several approaches involving covalent and non‐covalent functionalization methods have been applied . The ideal drug‐delivery vehicle would be biocompatible and biodegradable, able to navigate the circulatory system to reach the target and capable of releasing its therapeutic cargo only to the desired cells.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing mechanism of the composites containing TRGO‐Cu 2 O was attributed to the effective load transfer between epoxy and GO via interfacial adhesion,[5b] where the hydrophilic nature of GO can contribute to an improved dispersion of the TRGO‐Cu 2 O in the matrix, since a uniform nanofiller dispersion is known to enhance the mechanical performance of carbon‐based nanocomposites. [3a], Certainly, the tensile performance of the specimens with TRGO‐Cu 2 O also decreased with addition of capsules; as the addition of capsules to some extent can decrease the interfacial adhesion between matrix and reinforcing nanofiller, although an overall higher mechanical property in comparison to the pristine epoxy specimen was observed (Table ).…”
Section: Resultsmentioning
confidence: 99%